Detection of Bartonella bovis DNA in blood samples from a veterinarian in Mexico - Gamboa-Prieto, Jannete; Cruz-Romero, Anabel; Jiménez-Hernández, José A.; Ramos-Vázquez, José Rodrigo; Ballados-González, Gerardo G.; Romero-Salas, Dora; Pardío-Sedas, Violeta T.; Esparza-Gonzalez, Sandra C.; Becker, Ingeborg; Sánchez-Montes, Sokani (Revista do Instituto de Medicina Tropical de São Paulo, 2023)
The genus Bartonella encompasses 38 validated species of Gram-negative, facultative intracellular bacteria that colonize the endothelial cells and erythrocytes of a wide spectrum of mammals. To date, 12 Bartonella species have been recorded infecting humans, causing diseases of long historical characterization, such as cat scratch fever and trench fever, and emerging bartonellosis that mainly affect animal health professionals. For this reason, this study aimed to report a documented case of Bartonella bovis infecting a veterinarian from Mexico by the amplification, sequencing and phylogenetic reconstruction of the citrate synthase (gltA) and the RNA polymerase beta-subunit (rpoB) genes, and to report the natural course of this infection. To our knowledge, this work is the first to report the transmission of B. bovis via needlestick transmission to animal health workers in Latin America.